'[A]ll Sorts of Stiches': Looking at Detail in a Proclamation of Solomon Embroidery. (2nd January 2016) - Canavan, Claire
Abstract : This object lesson considers a mid- to late seventeenth-century embroidery, now held by the Ashmolean Museum, University of Oxford, which portrays the proclamation of Solomon. It assesses how viewers' attention was directed by the application of materials, textures and stitches, examining tensions between modes of viewing concerned with narrative, individual motifs, material content, skill and realism. It considers how these various forms of attention would have complemented or competed with one another, and how they may have appealed to different viewers in different contexts.